Social and Finance Security on Gig Workers’ Well-being with Occupational Satisfaction as an Intervening Variable - Azim, Abdul Mutalib Mohamed; Nadzri, Nazruzila Razniza Mohd; Awang, Nurulbahiah; Sulaiman, Tuan Fatma Tuan; Md Radzi, Mohd Shahril Nizam (Information Management and Business Review, 2024)
The rise in unemployment, digitization, and the flexibility of gig workers have propelled the growth of Malaysia’s gig economy. However, the well-being and occupational satisfaction of gig workers can be impacted by social and financial security concerns. This study looks at the well-being of Malaysian gig workers through the role of occupational satisfaction as a mediator, while social and financial security as independent variables. The results of a structured survey administered between November 2023 and February 2024 to 135 gig workers indicate that the well-being of Malaysian gig workers is rather low. This study found that occupational satisfaction acted as a mediator in the relationship between social and financial security and gig workers’ well-being. These results highlight how important it is to have both social and financial stability to enhance employee occupational satisfaction and thus, improve gig workers’ well-being.